Особливості правозастосовного процесу в діяльності органів внутрішніх справ - Слинько, Д. В.; Slynko, D. V.; Дмитро Слинько (Право і безпека. - 2015. - № 3 (58). - С. 97–102., 2015)
Досліджено правозастосовний процес як різновид юридичного процесу. Вивчено підходи до розгляду категорій «юридичний процес», «правозастосовний процес» та їх сутності, що склалися в юридичній науці. На підставі теоретичного аналізу юридичної літератури визначено особливості прояву правозастосовного процесу в діяльності органів внутрішніх справ.

Law enforcement process as a form of legal process is studied. Approaches to the categories of «suit», «law enforcement process» and their nature prevailing in legal science are researched. It is determined that the law enforcement process within internal affairs agencies is characterized by the following features: a masterful character, as it is the activity of a competent body or an official; this power-organizing activity is carried out only within the limits of powers; allows the possibility for the use of state compulsion; has individually personalized nature; has a procedural nature; has a creative, intelligent character; determines which particular rule of law must be used to the specific considered case; has legally character – is completed by the adoption of a special act (in most cases written) called an act of using the law norms or law enforcement act. It is established that the usage of law within internal affairs agencies – is a form of indirect, sometimes forced realization of the rights expressed in the professional activity of competent subjects to develop and decision-making, detailing the legal requirements for their practical implementation in the specific conditions of the objective reality. A definition of law enforcement process within internal affairs agencies is offered. It is carried out in the procedural order power-organizing activity of authorized agencies and officials, which is in the realization of legal norms regarding to specific subjects or specific life cases through individual and legal solutions using, if necessary, appropriate state compulsion.

Рассмотрен правоприменительный процесс как разновидность юридического процесса. Изучены подходы к пониманию категорий «юридический процесс», «правоприменительный процесс», их сущности, сложившиеся в юридической науке. На основании теоретического анализа юридической литературы определены особенности проявления правоприменительного процесса в деятельности органов внутренних дел.
Keywords: Держава і право. State and Law. Государство и право; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; юридичний процес; правозастосовний процес; процесуальна форма; правозастосовна діяльність; юридична діяльність; державний примус; реалізація права; стадії правозастосування; суб’єкт права; suit; law enforcement process; procedural form; law enforcement activity; legal activities; state compulsion; implementation of law; law enforcement stages; subject of law; Internal Affairs Agencies; юридический процесс; правоприменительный процесс; процессуальная форма; правоприменительная деятельность; юридическая деятельность; государственное принуждение; реализация права; стадии правоприменения; субъект права; органы внутренних дел